The Role of Humanitarian Organizations in Promotion of The Rights of Refugees in The Host Communities: A Case Study of Nyakabande Reception Centre. - Nyirabavakure, Catherine (Kabale University, 2024)
The study was to assess the role of humanitarian organizations in the promotion of the rights of refugees in the host communities. A case study of Nyakande reception center. The research study was guided by the following objectives; to find out the effects of refugees living in the refugee reception center, to examine the Challenges facing refugees living in the reception center, and to establish the strategies and possible ways of improving the conditions of refugees staying in the refugee in reception center. The researcher used the descriptive research design as appropriate for the study because the study was concerned with finding answers to a key question regarding the research topic under study. Using Krejcie and Morgan's table (1970), the researcher used a sample size of 52 who represented the whole study population under study. Data collection tools used included questionnaires and interview guides. Descriptive analysis was used to determine the proportions and frequency of the variables. The results were presented in the form of tables and figures. The highest number of respondents reported that the Nyakabande reception center is congested because of many refugees from different countries like Burundi and the Democratic Republic of Congo are living in that area. This accounted for 12(23%) of the total respondents who participated in the study. The respondents who accounted for 12(23%) and who participated in the study noted that security problems in general and crime rates, theft, murder, etc., in particular, are the main challenges facing refugees in settlement areas. The respondents added that other social problems such as prostitution and alcoholism are also claimed to rise in the Nyakabande reception center. The findings of the study on objective three showed that the highest number of respondents accounted for 12(23%) of the respondents who suggested that maintaining proper hygiene by frequently emptying garbage collection points should be emphasized regularly. The researcher concluded that the effort towards promoting refugee livelihoods is doomed to fail if refugees in Nyakabande reception center are not empowered to construct gainful livelihoods. To improve the socioeconomic status of the refugees in the Nyakabande reception center, and consequently their contribution to the host economy, there is a need to create an enabling environment that will promote individual and collective innovativeness and opportunities, and tap into the synergies and potential of the refugees.